Deglaciation history of Lake Ladoga (northwestern Russia) based on varved sediments. (21st February 2019) - Gromig, Raphael; Wagner, Bernd; Wennrich, Volker; Fedorov, Grigory; Savelieva, Larisa; Lebas, Elodie; Krastel, Sebastian; Brill, Dominik; Andreev, Andrei; Subetto, Dmitry; Melles, Martin
Abstract : Lake Ladoga in northwestern Russia is Europe's largest lake. The postglacial history of the Ladoga basin is for the first time documented continuously with high temporal resolution in the upper 13.3 m of a sediment core (Co1309) from the northwestern part of the lake. We applied a multiproxy approach including radiographic imaging, (bio‐)geochemical and granulometric analyses. Age control was established combining radiocarbon dating with varve chronology, the latter anchored to a correlated radiocarbon age from a lake close by. The age‐depth model reveals the onset of glacial varve sedimentation at 13 910±140 cal. a BP, when Lake Ladoga was part of the Baltic Ice Lake. Linear extrapolation of published retreat rates of the Scandinavian Ice Sheet provides a formation age of the Luga moraine close to Lake Ladoga's southern shore of 14.5–15.9 cal. ka BP, older than previously assumed. Varve sedimentation covers the Bølling/Allerød interstadial, the Younger Dryas stadial and the Early Holocene. Varve‐thickness variations, conjoined with grain‐size and geochemical variations, inform about the relative position of the Scandinavian Ice Sheet and the climate during the deglaciation phase. The upper limit of the varved succession marks the change from glaciolacustrine to normal lacustrine sedimentation and post‐dates the drainage of the Baltic Ice Lake as well as the formation of the Salpausselkä II moraine north of Lake Ladoga, by c . 250 years. The Holocene sediment record is divided into three periods in the following order: (i) a lower transition zone between the Holocene boundary and c . 9.5 cal. ka BP, characterized by mostly massive sediments with low organic content, (ii) a phase with increased organic content from c . 9.5 to 4.5 cal. ka BP corresponding to the Holocene Thermal Maximum, and (iii) a phase with relatively stable sedimentation in a lacustrine environment from c . 4.5 cal. ka BP until present.